Chronic tic cough in adults: a case report - Wanjing Yang; Zixin Qiu; Duanya Liu; Yajing Meng; Changjian Qiu (Frontiers in Medicine)
Chronic cough in adults is commonly caused by respiratory disorders (e.g., cough variant asthma, CVA), ear, nose and throat (ENT) disorders (e.g., postnasal drip), digestive disorders (e.g., gastroesophageal reflux disease, GERD), as well as anaphylaxis and allergy. Tic cough is infrequent in adults but warrants consideration in individuals who have excluded these somatic disorders and exhibit inadequate response to diagnostic treatments, especially those with a history of tic disorder or ongoing tic symptoms. In these cases, a multi-disciplinary treatment (MDT) for chronic cough that includes psychiatrists is recommended as the optimal management approach.